Non-Anthropocentrism? A Killing Objection. (1st May 1998) - Lynch, T.; Wells, D.
Abstract : To take the idea of a non-anthropocentric ethic of nature seriously is to abandon morality itself. The idea of humanity is not an optional extra for moral seriousness. Non-anthropocentric environmental ethicists mistake the kind of value non-human entities may bear. It is not moral value, but aesthetic value.